2003
DOI: 10.1042/bj20020743
|View full text |Cite
|
Sign up to set email alerts
|

A novel steroid receptor co-activator protein (SRAP) as an alternative form of steroid receptor RNA-activator gene: expression in prostate cancer cells and enhancement of androgen receptor activity

Abstract: We have cloned a cDNA coding for a novel steroid receptor co-activator protein termed SRAP from a rat prostate library. Although the nucleotide sequence of the SRAP has 78.2% identity to that of the human steroid receptor RNA activator (SRA), a novel RNA molecule which was reported to act as an RNA transcript without being translated into protein [Lanz, McKenna, Onate, Albrecht, Wong, Tsai, Tsai and O'Malley (1999) Cell 97, 17-27], the cDNA of SRAP is capable of generating a functional protein. Glutathione S-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 27 publications
2
88
1
1
Order By: Relevance
“…As well as the generation of small RNAs generated by cleavage, there are several precedents for ncRNAs being processed from an mRNA precursor, such as mirtrons from splice junctions (Ruby et al 2007) and endogenous siRNAs from mRNA duplexes (Okamura and Lai 2008). The ability to generate a range of noncoding transcripts from a coding precursor provides an intersecting avenue between the protein-coding and noncoding transcriptomes, thereby contributing to an increased blurring of the dichotomy between coding and regulatory transcripts (Kawashima et al 2003;ChooniedassKothari et al 2004;Dinger et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…As well as the generation of small RNAs generated by cleavage, there are several precedents for ncRNAs being processed from an mRNA precursor, such as mirtrons from splice junctions (Ruby et al 2007) and endogenous siRNAs from mRNA duplexes (Okamura and Lai 2008). The ability to generate a range of noncoding transcripts from a coding precursor provides an intersecting avenue between the protein-coding and noncoding transcriptomes, thereby contributing to an increased blurring of the dichotomy between coding and regulatory transcripts (Kawashima et al 2003;ChooniedassKothari et al 2004;Dinger et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…These receptors in turn exert their function on downstream targets by recruiting additional transcription and epigenetic factors, including ATP-dependent chromatin remodeling complexes and histone acetyltransferases (HATs) (Gronemeyer et al 2004). Interestingly, SRA is a bifunctional transcript, with one isoform functioning as ncRNA and another as mRNA that is translated into the protein SRAP (Kawashima et al 2003;Chooniedass-Kothari et al 2004), which may in turn antagonize the function of its noncoding counterpart (Hubé et al 2011). Conversely, an example of a lncRNA corepressor can be found at the cyclin D1 (CCND1) locus, where a series of independently transcribed, variable-length lncRNAs called ncRNA CCND1 are upregulated during stress (Klein and Assoian 2008;Wang et al 2008).…”
Section: Mechanisms Of Action: Finding Pattern In Chaosmentioning
confidence: 99%
“…Like the identification of new transcripts, however, just because an RNA is translated should not automatically be taken to mean that these peptides are functional, but could instead be "translational noise." Moreover, it would be a false dichotomy to maintain that a transcript must either be coding or be noncoding-the example of SRA/SRAP demonstrates that an RNA could potentially function at multiple levels, both as a ncRNA performing a regulatory role and as an mRNA for protein synthesis (Kawashima et al 2003;Chooniedass-Kothari et al 2004).…”
Section: Translated Lncrnas: Pervasive Translation or Gene Evolution mentioning
confidence: 99%
“…While all these studies refer to SRA as a noncoding RNA, we have previously demonstrated the existence of coding SRA RNA isoforms and corresponding endogenous SRA proteins, 12 highly conserved in vertebrates and expressed in breast cancer cell lines. 13,14 To date, no data are available on the possible role of the coding SRA RNA or SRAP in breast cancer cells or on their expression in human breast tumor tissues.…”
mentioning
confidence: 99%